A Sine-Cosine Algorithm Approach for Optimal PV and D-STATCOM Integration in Distribution Systems - Montoya , Oscar Danilo; Ram, Carlos Alberto; Grisales-Nore, Luis Fernando (Statistics, Optimization & Information Computing, 2024)
This study proposes the use of the Sine-Cosine Algorithm (SCA) to optimize the integration of solar photovoltaic (PV) systems and distribution static compensators (D-STATCOMs) in medium-voltage distribution networks. The SCA is applied to determine the optimal placement and sizing of both PV units and D-STATCOMs, utilizing a hybrid discrete-continuous approach for codifying the solutions. A power flow analysis, based on the successive approximations method, is employed to assess system performance, including voltage regulation and power distribution. The optimization is carried out using a master-slave framework, where the SCA handles the optimization process, and the power flow model evaluates the technical outcomes. Case studies on 33- and 69-bus systems reveal that the SCA achieves significant reductions in system losses, with improvements of approximately 35.5227% and 35.6331%, respectively. Moreover, the SCA demonstrates computational efficiency, outperforming other methods such as the Vortex Search Algorithm (VSA) and previous benchmarks. All simulations and validations were conducted using MATLAB 2024a, confirming the SCA’s robustness for this application.